Africa-Australia: making waves with Spore - Bradbury, Howard; Abbiv, Daniel (Technical Centre for Agricultural and Rural Cooperation, 2006)
One of the most gratifying aspects of Spore is the way it creates a ripple effect, putting readers in touch with one another and acting as a catalyst...